Decreased embryo developmental potential and lower cumulative pregnancy rate in men with multiple morphological abnormalities of the sperm flagella - Long, Rui; Wang, Meng; Zhou, Juepu; Mao, Ruolin; Wang, Cheng; Gu, Longjie; Chen, Yinwei; Jin, Lei; Zhu, Lixia (Frontiers in Endocrinology, 2024)
Objective: Multiple morphological abnormalities of the sperm flagella (MMAF) is characterized by abnormal flagellar phenotypes which is a particular kind of asthenoteratozoospermia. Previous studies have reported a comparable intracytoplasmic sperm injection (ICSI) outcome in terms of fertilization rate and clinical pregnancy rate in MMAF patients compared with non-MMAF patients; however, others have conflicting opinions. Assisted reproductive technology (ART) outcomes in MMAF individuals are still controversial and open to debate. Methods: Thirty-eight MMAF patients treated at an academic reproductive center between January 2014 and July 2022 were evaluated in the current retrospective cohort study and followed up until January 2023. Propensity score matching was used to adjust for the baseline clinical characteristics of the patients and to create a comparable control group. The genetic pathogenesis of MMAF was confirmed by the whole exome sequencing. The main outcomes were the embryo developmental potential, the cumulative pregnancy rate (CLPR), and the cumulative live birth rate (CLBR). Results: Pathogenic variants in known genes of DNAH1, DNAH11, CFAP43, FSIP2, and SPEF2 were identified in MMAF patients. Laboratory outcomes, including the fertilization rate, 2PN cleavage rate, blastocyst formation rate, and available blastocyst rate, followed a trend of decline in the MMAF group (P<0.05). Moreover, according to the embryo transfer times and complete cycles, the CLPR in the cohort of MMAF was lower compared with the oligoasthenospermia pool (P=0.033 and P=0.020, respectively), while no statistical differences were observed in the neonatal outcomes. Conclusions: The current study presented decreased embryo developmental potential and compromised clinical outcomes in the MMAF cohort. These findings may provide clinicians with evidence to support genetic counseling and clinical guidance in specific MMAF patients.